Analisis Pengaruh Drop Tegangan Baterai terhadap Waktu Starting pada Engine 4N15 Mitsubishi Triton - Ade Angraini Nasution; Yusep Sukrawan; Ridwan Adam Muhamad Noor (Universitas Proklamasi 45, 2026)
Starting performance in diesel engines is influenced by the battery’s ability to maintain voltage when the starter motor draws a high initial current. Excessive voltage drop can reduce cranking capability and affect the initial combustion process. This study aimed to analyze the effect of battery voltage drop on starting time in a Mitsubishi Triton equipped with a 4N15 diesel engine. The research used a field experimental method conducted directly on a vehicle with a 12-volt electrical system. Data were collected using a battery tester, scanner, and stopwatch through five tests consisting of three tests under normal operating conditions at 71–75 °C, one test under cold-engine conditions at 29 °C, and one test under hot-engine conditions at 89 °C. The main parameters observed were battery voltage drop and starting time. The results showed that normal operating conditions produced an average voltage drop of 3.25 V with an average starting time of 2.06 s. Cold-engine conditions at 29 °C produced the highest voltage drop of 4.23 V, while hot-engine conditions at 89 °C produced the lowest voltage drop of 3.08 V. The findings indicate that starting performance is influenced by voltage drop, battery condition, internal resistance, and CCA value. This study concludes that starting system analysis should consider voltage drop, minimum voltage during starting, and battery condition to obtain a more accurate analysis of starting performance.